In situ, on-resin synthesis of 8-Br/NH2 adeninyl peptide nucleic acid (PNA) oligomers and complementation studies with DNA - Vysabhattar, Raman; Ganesh, Krishna N. (Tetrahedron Letters, 2010)
A new, novel and efficient in situ synthesis of 8-aminoadeninyl PNA oligomers from corresponding 8-bromoadeninyl PNA oligomers is reported. The study of hybridisation properties of (8-Br/8-NH2) PNA oligomers with cDNA reveals substitution-site dependent stabilization of derived triplexes and duplexes. (C) 2010 Elsevier Ltd. All rights reserved.